BDNF Pretreatment of Human Embryonic-Derived Neural Stem Cells Improves Cell Survival and Functional Recovery after Transplantation in Hypoxic–Ischemic Stroke. Issue 12 (December 2015) - Rosenblum, Sahar; Smith, Tenille N.; Wang, Nancy; Chua, Joshua Y.; Westbroek, Erick; Wang, Kendrick; Guzman, Raphael
Intra-arterial neural stem cell (NSC) therapy has the potential to improve long-term outcomes after stroke. Here we evaluate if pretreatment of NSCs with brain-derived neurotrophic factor (BDNF) prior to transplantation improves cell engraftment and functional recovery following hypoxic–ischemic (HI) stroke. Human embryonic-derived NSCs with or without BDNF pretreatment (1 h, 100 ng/ml) were transplanted 3 days after HI stroke. Functional recovery was assessed using the horizontal ladder test. Cell engraftment was evaluated using bioluminescence imaging (BLI) and histological counts of SC121 + cells. Fluoro-Jade C (FJC) and NeuN stains were used to evaluate neuroprotection. The effect of BDNF on NSCs was analyzed using a migration assay, immunocytochemistry, Luminex proteomic assay, and RT-qPCR.BLI analysis demonstrated significantly higher photon flux in the BDNF-treated NSC group compared to untreated NSC ( p = 0.049) and control groups ( p = 0.0021) at 1 week after transplantation. Immunohistochemistry confirmed increased transplanted cell survival in the cortex ( p = 0.0126) and hippocampus ( p = 0.0098) of animals injected with BDNF-treated NSCs compared to untreated NSCs. Behavioral testing revealed that the BDNF-treated NSC group demonstrated increased sensorimotor recovery compared to the untreated NSC and control groups ( p < 0.001) over the 1-month period ( p < 0.001) following transplantation. A significant improvement in performance was found in the BDNF-treated NSC group compared to the control group at 14, 21, and 28 ( p < 0.05) days after transplantation. The cortex and hippocampus of the BDNF-treated NSC group had significantly more SC121 + NSCs ( p = 0.0125, p = 0.0098), fewer FJC + neurons ( p = 0.0370, p = 0.0285), and a higher percentage of NeuN + expression ( p= 0.0354) in the cortex compared to the untreated NSC group. BDNF treatment of NSCs resulted in significantly greater migration to SDF-1, secretion of M-CSF, VEGF, and expression of CXCR4, VCAM-1, Thrombospondins 1 and 2, and BDNF. BDNF pretreatment of NSCs results in higher initial NSC engraftment and survival, increased neuroprotection, and greater functional recovery when compared to untreated NSCs.